2022
DOI: 10.1002/aenm.202102951
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Surface Oxygen for Lithiation and Morphology Evolution during Calcination of High‐Nickel NMC Cathodes

Abstract: both thermally and electrochemically. [2][3][4] Cathodes with high nickel content (y > 0.8) are also more difficult to synthesize, requiring oxygenrich calcination conditions, and are more prone to lithium/transition-metal siteexchange. [5][6][7][8][9] Thermal parameters play a critical role in the morphology of the final cathode, which strongly affects its rate performance and cyclability. Advanced understanding of the underlying chemistry during synthesis is necessary to enable Ni-rich cathodes to operate cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…Regardless of the processing conditions, the secondary particles of all NCM90 cathode materials exhibit a spherical morphology with an average secondary particle size of ∼10 μm. The morphological changes in the DX-NCM90 cathode materials observed here agree with the recent literature, which suggests that increased oxygen surface coverage, such as high oxygen pressure here, leads to small primary particles due to slowed particle growth, and the details are shown in Supporting Information . As shown in Table S1, for the same equipment and temperature, the mole of oxygen is directly proportional to the pressure; e.g., the amount of oxygen at 5 MPa is almost 50 times that at an ambient oxygen atmosphere of ∼0.1 MPa.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Regardless of the processing conditions, the secondary particles of all NCM90 cathode materials exhibit a spherical morphology with an average secondary particle size of ∼10 μm. The morphological changes in the DX-NCM90 cathode materials observed here agree with the recent literature, which suggests that increased oxygen surface coverage, such as high oxygen pressure here, leads to small primary particles due to slowed particle growth, and the details are shown in Supporting Information . As shown in Table S1, for the same equipment and temperature, the mole of oxygen is directly proportional to the pressure; e.g., the amount of oxygen at 5 MPa is almost 50 times that at an ambient oxygen atmosphere of ∼0.1 MPa.…”
supporting
confidence: 88%
“…DX-NCM90 (X ≥ 5) cathode materials, without doping or coating, show excellent electrochemical cycling performance, signifying the vital role of primary particle size and size distribution. Furthermore, compared to using doping or coating to modify the morphology of high-nickel layered cathode materials, which introduce an inevitable loss of capacity due to the introduction of electrochemically inactive materials, the DX-NCM90 (X ≥ 5) cathode materials engineered under high oxygen pressure show an excellent high and reversible capacity. , This study also provides a method based on deep learning for obtaining intercomparable information about primary particles (e.g., number per area, size, and standard deviation). In addition, improving the electrochemical performance of high-Ni cathodes without the need for foreign ions is particularly interesting amid the ever-increasing price of globally unevenly distributed or depleted dopant resources.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A notable difference in the curves can be observed between 150 and 300 °C. PR and 5F display firm endothermic peaks at ∼260 °C, which can be attributed to the decomposition of transition-metal hydroxides to oxides and the subsequent generation of H 2 O vapor. , This conversion typically precedes lithiation, which occurs at or after the melting point of the lithium source (460 °C for pure LiOH), although some reports suggested that a solid-state lithiation of the oxide can occur at temperatures below the melting point . In the case of 5Br and 5Cl samples, the endothermic peak intensity is mostly suppressed, which suggests that simultaneous exothermic reaction(s) occur within this temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…In real-world manufacturing applications the highly simplified model represented by the mapping X → Y from control space to design space can be clouded. For example, a product's desired design properties might require so-called ex situ measurements at facilities external to the manufacturing facilities [26], and this requirement can in- troduce long time latencies in the measurement of the experimental response function that vitiate the practical application of a direct TAD-based methodology. In such cases one can still envision a place for the TAD algorithm in the design workflow.…”
mentioning
confidence: 99%